Fungos amazônicos com potencial para degradar Chorume in natura obtido do lixão municipal de Parintins - Nunes, Adriana da Silva (2012)
There are several techniques for treating toxic effluents as manure, but the white rot fungi have achieved notoriety in recent decades in fits of continuing environmental degradation. But little is known about the fungi of the Amazon region and their behavior in culture medium supplemented with toxic compounds. The aim of this study was to evaluate the potential of fungi in the degradation of Amazonian fresh manure obtained from the municipal landfill Parintins / AM. The strain Pycnoporus sanguineus and FV-12 and were inoculated into culture media different to the first glucose and different concentrations of slurry (M1) and second with the addition of inducer seringaldazine (M2). The strains grew up in different culture media, P. sanguineus obtained the highest mycelial growth in M2 medium, while FV-12 stood out in the middle of M1. However, other nutritional and physiological factors affecting the growth of fungi in a medium containing toxic compounds. P.sanguineus produced a larger amount of biomass is increased as the concentration of the slurry (1%, 2%, 4%) in the middle, however, the opposite behavior is observed in treatment with the fungus FV-12. With regard to the degradation of total protein FV-12 had higher percentages, but smaller in relation to inhibition of toxicity and discoloration, that effect P.sangineus said fungus is possibly by the formation of byproducts resulting from the more toxic action of the fungus FV-12. This in turn, increased levels of excreted MnP and LiP within thirty days, noting combined action of these enzymes, which may have influenced the further degradation of total protein per FV-12. In relation to the enzyme laccase were detected low levels of activity in the periods tested for P. sanguineus and FV-12, possibly due to influences of factors such as incubation time and carbon source. The fungus P.sanguineus had the highest percentage of degradation of manure, and their possible application in the treatment of manure. Keywords: Slurry, Fungi Amazon, Degradation, Oxidative Enzymes, Parintins/AM.